2022
DOI: 10.1177/13548565221074804
|View full text |Cite
|
Sign up to set email alerts
|

Twitch, Fish, Pokémon and Plumbers: Game live streaming by nonhuman actors

Abstract: In this exploratory paper, we consider the phenomenon of gameplay live streaming by nonhumans. The live streaming of games, exemplified by the platform Twitch.tv, has emerged in recent years as a major and growing component of gaming culture. Although previous research has addressed some agential dimensions of streaming, scholarship has yet to examine the unusual phenomenon of watching streams lacking any kind of human agent. Ordinarily a human streamer operates gameplay and directs the flow of conversation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For example, based on footage shared on social media the game Stray (BlueTwelve Studio 2022) was enjoyed by human players as well as their feline companions (@catswatchstray on Twitter). Moreover, in a recent article, Mark Johnson and Nathan Jackson (2022) investigate the notion of nonhuman game streamers, and they offer as a case study "a live fish observed by a motion tracker 'play[ing]' a game of Pokémon Red" (436). As the authors point out, nonhuman players raise important questions about the constantly shifting definitions of agency that inform contemporary gaming culture.…”
Section: Human-animal Relationsmentioning
confidence: 99%
“…For example, based on footage shared on social media the game Stray (BlueTwelve Studio 2022) was enjoyed by human players as well as their feline companions (@catswatchstray on Twitter). Moreover, in a recent article, Mark Johnson and Nathan Jackson (2022) investigate the notion of nonhuman game streamers, and they offer as a case study "a live fish observed by a motion tracker 'play[ing]' a game of Pokémon Red" (436). As the authors point out, nonhuman players raise important questions about the constantly shifting definitions of agency that inform contemporary gaming culture.…”
Section: Human-animal Relationsmentioning
confidence: 99%
“…The article by Mark R. Johnson and Nathan J. Jackson (‘Twitch, Fish, Pokémon and Plumbers: Game live streaming by nonhuman actors’) looks at nonhuman agencies in streaming cultures (Johnson and Jackson, 2022). In particular, the authors focus on four interventions involving the streaming of automated play sessions on Twitch: two streaming channels showing an automated ‘trading’ system of Pokémon, the fictional creatures by Nintendo; a modified stage made with Super Mario Maker that runs by itself in a 4-second loop, where Mario dies in each reiteration unless a ‘one in a 7.5 million’ event takes place; and the streaming of a Pokémon game played through the involuntary inputs of a fish in a tank, monitored by a webcam with motion-capture software.…”
Section: Article Summariesmentioning
confidence: 99%